The measurement of crisis management strategies in tourism. Development and validation of a scale - Singh, Ramjit; Nazki, Adil Amin (Turyzm/Tourism, 2023)
Crises and disasters pose significant obstacles to the socio-economic progress of any destination, especially in the tourism sector. Although travel and tourism are among the world’s most prominent economic sectors, they are susceptible to various hindrances, such as natural disasters, political instability and unpredictable terrorist attacks, which can harm the destination’s reputation and decrease tourist arrivals. While humans cannot control these incidents, they can implement measures, strategies and activities to mitigate their impact. This research aims to create and validate a scale for crisis management strategies in tourism using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). A 58-item questionnaire was developed based on literature reviews and interviews with destination marketing organizations (DMO’s), which was then reduced to 47 items after content validation by experts and the target population. EFA was conducted on data from 346 tourism stakeholders, resulting in six discrete factors: media, promotional measures, partnering, security and awareness, innovative marketing, and finance. Finally, AMOS 21 was used to perform confirmatory factor analysis, and the crisis management strategies scale developed retained 38 items.